Infant Feeding Practices Among Mothers Of High And Low Socio-Economic Group In Selected Areas of Dhaka City (Journal of Shaheed Suhrawardy Medical College, 2012)
Objectives: To study the patterns of infant feeding practice among the mothers of high and low socio-economic groups.Design: The descriptive cross-sectional study was conducted among a cross section of mothers with infant of high socioeconomic group, the residents of Sobhanbag government colony & Panthopath Green road residential area and low socioeconomic group slum area of Raver bazar, Dhaka. The study was carried out during the period of October '2007 to May '2008. Results: Total 104 children, 41.3% were in 9 months or more age and of them 40.3% were in high socioeconomic group & 42.3% were in low socioeconomic group. About 96.2% mothers from high socio-economic group provide either fullv or partiallv correct answer to the question regarding the benefit of colostrums and 59.7% from low-socio-economic group. Again, among the mothers from high socioeconomic groups 90.4% and 61.5% stated fully or partiallv correct answer about the benefits of breast feeding & the optimum weaning time respectively. Colostrums intake practice was observed 94.2% mothers of high socio-economic group and 67.3% of low of socioeconomic group. Breast milk as the first food to their babies was given 71.2% mothers of high & 65.4% of low socioeconomic group. The rate of exclusive breast feeding among mothers of 2-3 months baby from high socio-economic group was found 41.2% and low socio-economic group 34.4%. Conclusion: From this study it was evident that mothers of low socioeconomic group have poor knowledge regarding the infant feeding practices. So, Breast feeding campaign should he directed to the low socioeconomic group bv more effective wav. Strengthening of breast-feeding counseling at primarv health care center in both rural and urban area can play significant role in this regard. Journal of Shaheed Suhrawardy Medical College Vol 2No.1 June 2010 page 17-21 DOI: http://dx.doi.org/10.3329/jssmc.v2i1.12346